Effects of vacancy defects on electronic properties of 2D group-IV Tellurides (XTe, X = Si, Ge, Sn and Pb). (January 2020) - Guo, Hao; Jiang, Wentao; She, Qianqian; Fan, Haidong; He, Xiaoqiao; Tian, Xiaobao
Abstract: Vacancy defects are almost inevitable in the synthesis process and have important effects on the physical properties of two-dimension (2D) materials. Using first-principles calculations based on the density functional theory (DFT), we investigated the effects of vacancy defects (X-vacancy and Te-vacancy) on the geometry structures, mechanical and electronic properties of 2D group-IV Tellurides (XTe, X = Si, Ge, Sn and Pb). Results demonstrate that the X-vacancy is prone to form than Te-vacancy under Te-rich growth condition. The X-vacancy and Te-vacancy defects can be avoided under X-rich and Te-rich growth conditions, respectively. Moreover, vacancy defects have weak effects on the crystal structures and mechanical properties of XTe monolayers. It should also be noticed that the XTe monolayers with X-vacancy show p-type doping characteristics due to extra holes. However, the Te-vacancy XTe monolayers maintain indirect bandgap semiconductors except for SiTe monolayer. Particularly, the SiTe monolayer can be converted from semiconductor to semimetal by Te-vacancy. Furthermore, the uniaxial strain can also effectively regulate the electronic properties of perfect and defective XTe monolayers. These theoretical results provide valuable insights into identification of vacancy defects in the fabrication process and applications of 2D Tellurides. Highlights: The X-vacancy in XTe monolayers (X=Si, Ge, Sn and Pb) can be avoided under X-rich growth conditions. The XTe monolayers with X-vacancy (X=Si, Ge, Sn and Pb) show p-type doping characteristics due to extra holes. The Te-vacancy XTe monolayers (X=Ge, Sn and Pb) maintain indirect bandgap semiconductors. The SiTemonolayer can be converted from semiconductor to semimetal by Te-vacancy. The electronic properties of defective XTe monolayers (X=Si, Ge, Sn and Pb) can be effectively regulated by uniaxial strain.